TINDAKAN SCALING DAN PENYULUHAN SEBAGAI UPAYA MENINGKATKAN ORAL HYGIENE DAN TINGKAT PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT PARA SISWA SMP NO 2 MARGA KABUPATEN TABANAN 2018 - Maria Martina Nahak; Regina Tejasulaksana; Ni nengah Sumerti; Anak Agung Gede Agung (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
Dental health and periodontal tissue are very critical in adolescence. Teenage oral cavity problems are caused due to poor dental and oral hygiene and irregular eating patterns. Promotion of dental and oral health in adolescents can be done through counseling both individuals and group counseling, while those who have tartar problems need to get scaling. The purpose of this study is to improve oral hygiene and knowledge about the maintenance of oral and dental health of students of SMP No. 2 Marga in Tabanan Regency in 2018. Method of this study is one group pretest and posttest without control group design. Data was taken before an action and evaluating it after that. The result of this study showed that there is an increased in the average value of knowledge of students before and after getting counseling with an average value before counseling was equal to 57.74 with less criteria and after counseling increased to 72.02 with good criteria. The results of statistical analysis of the value of knowledge indicate that the increase is not significant. The average OHI-S value of students decreased from 2.36 to 1.29 with moderate criteria, and the results of statistical analysis showed that the decline was significant, which means that with scaling action there was a significant increase in students' dental and oral hygiene, so it can be concluded that scaling and counseling can improve dental and oral hygiene of students and increase knowledge about how to maintain dental and oral hygiene.